Sustainability consciousness level among pre-service biology teacher - Melta, Defrian; Lufri, Lufri; Arsih, Fitri; Fuadiyah, Sa’diatul (Assimilation: Indonesian Journal of Biology Education, 2025)
Sustainable Development Goals (SDGs), established by the United Nations in 2015, aim to address global challenges such as poverty, inequality, and climate change. Achieving these goals necessitates sustainability consciousness, which encompasses awareness, knowledge, attitudes, and behaviors towards sustainable development. This study evaluates the sustainability consciousness among pre-service Biology Education teacher students at Universitas Negeri Padang using the Sustainability Consciousness Questionnaire (SCQ). The SCQ, adapted from Gericke et al. (2018), includes 50 statements across economic, social, and environmental dimensions, and assesses sustainability knowingness, attitudes, and behaviors using a 4-point Likert scale. Data analysis involved descriptive statistics to categorize respondents into low, medium, and high sustainability consciousness levels. The results reveal that 88.5% of students possess medium sustainability consciousness, 7.7% exhibit low consciousness, and 3.8% demonstrate high consciousness. The study also found that sustainability consciousness is highest in the social dimension, with strong attitudes and behaviors towards social sustainability, while environmental and economic dimensions showed variability. These findings highlight the need for targeted educational interventions to enhance sustainability consciousness among pre-service teachers, crucial for embedding sustainability into higher education curricula.